Achieving uterine auto‐transplantation in a sheep model using iliac vessel anastomosis: a short‐term viability study. (25th December 2014) - Saso, Srdjan; Petts, Gemma; Thum, Meen‐Yau; Corless, David; Boyd, Michael; Noakes, David; Del Priore, Giuseppe; Ghaem‐Maghami, Sadaf; Smith, James Richard
Abstract Objective To investigate, develop and evaluate anatomical, surgical and anastomotic aspects necessary for a successful uterine transplant in a large‐animal model. Design Sheep model; longitudinal study involving five ewes. Setting Royal Veterinary College, London, UK. Population Five ewes of proven fertility. Methods The uterine allograft along with the internal iliacs, and uterine arterial and venous tree all intact were harvested en bloc. An end‐to‐side anastomosis was performed between the external iliac vessels and the internal iliac vessels of the graft using 6‐0 polypropylene. Successful reperfusion of the graft was initially judged by the color shift of the uterus during reperfusion. Blood flow past the venous and arterial anastomotic sites was also ensured by visual inspection, together with pulse oximetry and multispectral imaging. Main outcome measures Operative details (retrieval, ischemic, clamping, reperfusion and recipient hysterectomy duration); physiological profiles; gross morphology and histopathology. Results Five autotransplants were performed. One procedure was abandoned because of the inappropriate size of sheep model. Another procedure was halted because the animal suffered from respiratory failure in the immediate intra‐operative period. Three transplants were completed. In those, at least two of four possible anastomoses were finished and the grafted uteri demonstrated immediate perfusion and appropriate viability 45 min post‐operatively. Conclusions Internal to external iliac vessel anastomoses are an acceptable surgical technique that should be applied in a human model to ensure adequate subsequent uterine perfusion.